Agricultural internet of things and decision support for precision smart farming - Castrignano, Annamaria; Buttafuoco, Gabriele; Khosla, Raj; Mouazen, Abdul M.; Moshou, Dimitrios; Naud, Olivier (Academic Press, 2020)
Agricultural Internet of Things and Decision Support for Smart Farming reveals how a set of key enabling technologies (KET) related to agronomic management, remote and proximal sensing, data mining, decision-making and automation can be efficiently integrated in one system. Chapters cover how KETs enable real-time monitoring of soil conditions, determine real-time, site-specific requirements of crop systems, help develop a decision support system (DSS) aimed at maximizing the efficient use of resources, and provide planning for agronomic inputs differentiated in time and space. This book is ideal for researchers, academics, post-graduate students and practitioners who want to embrace new agricultural technologies